Enhanced Vaterite And Aragonite Crystallization At Controlled Ethylene Glycol Concentrations - Derya Kapusuz; Batur Ercan; Çağatay Mert Oral (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi, 2019)
Calciumcarbonate (CaCO3) has three distinct anhydrous polymorphs, namelyvaterite, aragonite and calcite. Although there is a high demand for aragoniteand vaterite polymorphs for biomedical use, their unstable nature makes itchallenging to synthesize them compared to calcite, which is the most stableform of CaCO3. Despite the remarkable effort on stabilizing vateriteand aragonite polymorphs in aqueous solutions, phase-pure vaterite andaragonite polymorphs have not been synthesized yet, without referring to theuse of additives, surfactants or elevated temperatures. Herein, the effect ofethylene glycol (EG) concentration and temperature on the formation of vateriteand aragonite particles were investigated at 25 °C and 70 °C. Results showedthat 60% EG containing precursor solution -without any other additive- canprevent vaterite/aragonite-to-calcite transformation regardless of thesynthesis temperature. Furthermore, the size of CaCO3 particlesdecreased as EG concentration increased and it reached its minimum averagevalues at 80% EG. The results of this study revealed the potential use of theproposed synthesis route to stabilize vaterite and aragonite polymorphs, tailortheir content, morphology and size without using any additives, surfactants andelevated temperatures.